Changes of miR-130a and ET-1 and Their Predictive Value for In-Stent Restenosis after Percutaneous Coronary Intervention - Hongliang LIU; Hao QIAN; Junlin MA; Qiming DAI; Mingyue JI (Tehran University of Medical Sciences, 2020)
Background: To explore the changes of miR-130a and endothelin -1 (ET-1) and their predictive value for in-stent restenosis (ISR) after percutaneous coronary intervention (PCI). Methods: Overall, 253 patients with coronary heart disease (CHD) treated with PCI in Lianshui County People's Hospital, Huaian, China from April 2013 to May 2016 were selected. The changes of miR-130a and ET-1 levels before and after PCI were compared. The predictive value of miR-130a and ET-1 for ISR was analyzed by receiver operating characteristic (ROC) curves, and the correlation between ISR and miR-130a, ET-1 was analyzed by Kaplan-Meier (K-M) curve. The risk factors of ISR in CHD patients were evaluated by logistics regression analysis. Results: The postoperative levels of miR-130a and ET-1 were significantly increased (P<0.05). The levels of miR-130a and ET-1 in peripheral blood of patients with ISR were higher than those in patients without ISR (P<0.05). The ROC curves showed that the area under curve (AUC), sensitivity, specificity and critical value of miR-130a in predicting ISR were respectively 0.912, 92.02%, 73.47%, 1.457 pmol/L, and those of ET-1 were 0.814, 87.63%, 63.27%, 2.245 pmol/L, respectively. The K-M curve showed that the incidence of ISR in patients with high expression of miR-130a or ET-1 was significantly higher than that in patients with low expression (P<0.05). miR-130a and ET-1 were independent risk factors for ISR (P<0.05). Conclusion: MiR-130a and ET-1 have high predictive value for ISR after PCI and are independent risk factors for CHD patients, which are worthy of clinical application.